If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 + -4x = 48 Reorder the terms: 12 + 6x + -4x = 48 Combine like terms: 6x + -4x = 2x 12 + 2x = 48 Solving 12 + 2x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2x = 48 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 48 + -12 2x = 48 + -12 Combine like terms: 48 + -12 = 36 2x = 36 Divide each side by '2'. x = 18 Simplifying x = 18
| .5n=-8.3 | | x+163+38=2x+125 | | d/5=7 | | 2x^2+6x^2+6x=6x+40 | | 5n^2+34n-48=0 | | 5n^2+34-48=0 | | 9x^2+12+3=0 | | 3(4x^2-6x-7)=0 | | 10*54p= | | 4=0.4(3d-5-5) | | 43y=16 | | 2a^2-13a-7=0 | | 13(t+4)=2(t-10)-27 | | 2(4x+5)=-19+13 | | 4=0.4(3x-5-5) | | 11z/16+7z/8=5/15 | | 35=8x+138 | | .625j=-10 | | 6(y-8)-y=2(-9-y) | | x+x-40=90 | | 4(2t+2)-9=2 | | 19x-5=13x-35 | | p-18=-29 | | 6-6x=-3x-6 | | x+.75=2x-.75 | | 0.333333333x+y=4 | | 2r+8/4=3r-9/3 | | x+x+40=90 | | 1/4[4-x]=10+2x | | -1=41+x/3 | | 5x+7(9x+8)= | | 2x-3(x-4)=2(3-2x)+2 |